2017
DOI: 10.21141/pjp.2017.019
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into the Histopathology of Oral Neoplasms with Basaloid Morphology and a Working Classification

Abstract: Basal cell tumors (BCT) are tumors usually derived from pluripotential stem cell compartments of the basal layer of epidermis and/or oral epithelium. BCTs are infrequent entities in the oral cavity and are not discussed separately in general and oral pathology. A literature review did not reveal any classification of tumors with basaloid morphology. This paper is an attempt to categorize the oral neoplasms with basaloid morphology and discuss their differential diagnoses in detail. A review of the literature w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…[ 9 20 ] Histopathologically, differential diagnosis can be intraoral basal cell carcinoma and basal cell adenoma. [ 2 25 ] Immunohistological (IHC) studies have been conducted on variants of ameloblastoma including six cases of BCA. Cytokines were consistent with all variants of ameloblastoma, but an elevation of p53 and ki-67 was evident in the basal cell variant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 20 ] Histopathologically, differential diagnosis can be intraoral basal cell carcinoma and basal cell adenoma. [ 2 25 ] Immunohistological (IHC) studies have been conducted on variants of ameloblastoma including six cases of BCA. Cytokines were consistent with all variants of ameloblastoma, but an elevation of p53 and ki-67 was evident in the basal cell variant.…”
Section: Discussionmentioning
confidence: 99%
“…Jawad and Abdullah conducted a study on basal cell variant of ameloblastoma and basal cell carcinoma using a panel of markers, and they found MMP-2 is higher in basal cell ameloblastoma whereas p53 and MMP-9 were increased in basal cell carcinoma. [ 25 ] Due to the scarcity of data, the exact nature of BCA cannott be predicted. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…The histological differential diagnoses include BCA, adenoid cystic carcinoma (AdCC), intra-oral basal cell carcinoma (IOBCC), basaloid squamous cell carcinoma (BSCC) and basal cell ameloblastoma (Bajpai and Pardhe, 2017). On histopathological examination, the tumour may exhibit solid, tubular, trabecular, cribriform and membranous patterns.…”
Section: Discussionmentioning
confidence: 99%
“…We could not perform staining with CK 19 as the antibody is not available in our centre. Our review of literature (Table 1) showed that BCA mostly occurred in adults (from the 3rd decade Table 2 The clinical, histological and IHC features of oral basal cell tumours 1,18,[31][32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…Bajpai and Pardhe proposed a simple working classification for oral basal cell tumours. There were three groups which included tumours arising from (i) oral epithelium [intraoral basal cell carcinoma (IOBCC), BSCC], (ii) odontogenic epithelium (BCA, EA), and (iii) minor salivary glands [solid adenoid cystic carcinoma (ACC), basal cell adenoma (BCAd), basal cell adenocarcinoma (BAC)]. IOBCC is defined as malignancy of the skin originating from the basal layer of the epithelium predominantly in sun exposed areas.…”
Section: Discussionmentioning
confidence: 99%